2018
DOI: 10.1007/s11051-018-4314-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of magnesium oxide and magnesium hydroxide nanoparticles in physiologically relevant fluids

Abstract: Magnesium oxide (MgO) and hydroxide [Mg(OH) 2 ] are conventionally considered insoluble in water and stable at high temperatures. However, in this study, we found significant dissociation of MgO and Mg(OH) 2 into ions when they were immersed in different physiologically relevant solutions in the form of 20nm and 10-nm nanoparticles respectively, under standard cell culture conditions in vitro, i.e., a 37°C, 5% CO 2 /95% air, sterile, humidified environment. The change in Mg 2+ ion concentrations and pH measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 39 publications
(62 reference statements)
3
24
0
Order By: Relevance
“…Indeed, the dissociation of Mg(OH) 2 is known to be heavily influenced by pH and temperature, with the physiological pH (7.2–8.2) promoting its dissociation. 33 The media pH of NP concentrations between 156.3 and 19.5 μg/mL ( Figure 4 ) corresponds to this range, thus explaining higher NP dissociation in low concentrations. Indeed, another study confirmed full degradation, hence 100% dissociation, of Mg(OH) 2 NPs at 200 μg/mL.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, the dissociation of Mg(OH) 2 is known to be heavily influenced by pH and temperature, with the physiological pH (7.2–8.2) promoting its dissociation. 33 The media pH of NP concentrations between 156.3 and 19.5 μg/mL ( Figure 4 ) corresponds to this range, thus explaining higher NP dissociation in low concentrations. Indeed, another study confirmed full degradation, hence 100% dissociation, of Mg(OH) 2 NPs at 200 μg/mL.…”
Section: Discussionmentioning
confidence: 81%
“…In an examination of antimicrobial activities of biodegradable magnesium based materials, Nguyen et al [ 19 ] identified several possible mechanisms of antimicrobial activity that may occur as a single activity or in tandem, including oxidative stress, interruption of quorum sensing processes, and changes in Ca 2+ ion concentrations in extracellular fluids that result from the degradation of magnesium. The effects of these activities may also be dependent on the thickness of Gram-positive and Gram-negative peptidoglycan structures and the presence of an outer cell membrane in Gram-negative bacteria [ 20 ]. Additionally, although magnesium metal degradation leads to the release of hydrogen ions (H + ) into the surrounding solution, here it was shown that inhibition of bacterial growth was not a result of the effects of hydrogen ion release [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of these activities may also be dependent on the thickness of Gram-positive and Gram-negative peptidoglycan structures and the presence of an outer cell membrane in Gram-negative bacteria [ 20 ]. Additionally, although magnesium metal degradation leads to the release of hydrogen ions (H + ) into the surrounding solution, here it was shown that inhibition of bacterial growth was not a result of the effects of hydrogen ion release [ 19 , 20 ]. Lock et al [ 21 ] identified a significant decrease in bacterial proliferation when magnesium alloys degraded in artificial urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmentally friendly nanomaterials have recently become vital in a variety of research and development domains. Magnesium oxide (MgO) and magnesium hydroxide (Mg(OH) 2 ) are two of the most environmentally friendly materials when compared to other materials [3][4][5]. For properties such as flame resistance, dielectric resistance, and mechanical strength; and micro structural properties such as porosity, large surface area catalysis, acid-base sites, and gas adsorption, MgO is well received in industrial applications such as ceramics, cement, and water treatments [2,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%